Resource predictability drives interannual variation in migratory behavior in a long-lived bird. (30th November 2021) - Baert, Jan M; Stienen, Eric W M; Verbruggen, Frederick; Van de Weghe, Nico; Lens, Luc; Müller, Wendt
Abstract: There is a growing awareness that experience may play a major role in migratory decisions, especially in long-lived species. However, empirical support remains to date scarce. Here, we use multiyear GPS-tracking data on 28 adult Lesser Black-backed Gulls ( Larus fuscus ), a long-lived species for which migratory strategies typically consist of a series of long stopovers, to assess how experience affects interannual variation in stopover selection. We expect that food source reliability should play a pivotal role, as it both reduces the uncertainty on food availability across years, and enables for more efficient foraging during stopovers by reducing searching efforts. We found that during stopovers gulls indeed developed high fidelity to particular foraging locations, which strongly reduced the daily distance travelled for foraging. When revisiting stopovers in consecutive years, birds used over 80% of foraging locations from the previous year. Although the average fidelity to stopovers across years was a high as 85%, stopovers where birds showed high foraging site fidelity were up to 60% more likely to be revisited compared to stopover with low foraging site fidelity. Accordingly, birds using more stopovers with reliable foraging opportunities showed significantly less interannual variation in their stopover use than birds using stopovers with less reliable foraging opportunities. Our results thus highlight the need to further deepen our understanding of the role of cognitive processes in individual variation in migratory behavior. Abstract : We use GPS tracking data on 28 adult Lesser Black-backed Gulls to show how these long-lived birds benefit from experience during migration. We found that stopover fidelity across years strongly depended on food source reliability. Birds using more reliable food sources thereby showed more consistent migratory behavior across years and covered significantly less distance while foraging during stopovers.